Arsenic Trioxide Modulates the Central Snail Neuron Action Potential - Guan-Ling Lu (Journal of the Formosan Medical Association, 2009)
The electropharmacological effect of arsenic trioxide (As2O3) is unknown. The present study investigated the effects of As2O3 on spontaneous neuronal impulse activity. Methods: Intracellular recordings and the two-electrode voltage clamp method were used to study the effect of As2O3 on the RP4 neuron, the number 4 neuron in the right partial ganglion of the giant African snail (Achatina fulica Ferussac). Results: The RP4 neuron generated spontaneous action potentials, which were affected by As2O3 in a concentration-dependent manner. Extracellular application of 1 or 3 mM As2O3 decreased the frequency of spontaneously generated action potentials. At 10 mM, As2O3 first depolarized and then elicited irreversible bursts of potential (BoPs) at 60 minutes after administration. At 30 mM, As2O3 depolarized the resting membrane potential and abolished the spontaneous action potentials. The BoPs elicited by 10 mM As2O3 were blocked when neurons were pretreated with phospholipase C (PLC) inhibitors (10 mM U73122 or 3 mM neomycin). The BoPs elicited by As2O3 remained unchanged in the presence of KT5720, verapamil, or calcium replacement solution. Voltage-clamp studies revealed that 10 mM As2O3 decreased the fast inward current and had no effect on the steady-state outward current of the neuron. Conclusion: As2O3 at 10 mM elicits BoPs in central snail neurons and this effect may relate to the PLC activity of the neuron, rather than protein kinase A activity, or calcium influxes of the neuron. As2O3 at higher concentration irreversibly abolishes the spontaneous action potentials of the neuron.